1961
DOI: 10.1161/01.res.9.3.531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Work Loads Applied at Various Times in the Cardiac Cycle of the Isolated Dog Heart

Abstract: Effects of work loads imposed at various times in the cardiac cycle were studied in isolated left ventricle preparations of dog hearts. In six preparations, resistance loads were applied briefly at times in ventricular systole; in six, volume loads were applied briefly at times in ventricular diastole; in six, experimental aortic regurgitation was produced. Simultaneous recorc1s of left ventricular and aortic pressures and electrocardiograms were used to cletermilie the subdivisions of the cardiac cycle and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1962
1962
1988
1988

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…On the other hand, an acutely induced increase in the peak ventricular pressure or increase in heart rate tended to augment the negative PD (Table III) (18). The observations of these and other investigators (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) are all compatible with the view that the rate at which ventricular pressure is developed reflects a fundamental property of contracting myocardium. Accordingly, it was thought that measurement of this parameter would provide an approach to the study of ventricular contractility in intact, unanesthetized man.…”
Section: Negative Pdsupporting
confidence: 67%
See 2 more Smart Citations
“…On the other hand, an acutely induced increase in the peak ventricular pressure or increase in heart rate tended to augment the negative PD (Table III) (18). The observations of these and other investigators (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) are all compatible with the view that the rate at which ventricular pressure is developed reflects a fundamental property of contracting myocardium. Accordingly, it was thought that measurement of this parameter would provide an approach to the study of ventricular contractility in intact, unanesthetized man.…”
Section: Negative Pdsupporting
confidence: 67%
“…However, Zeig, Buckley and Porter have recently shown that contraction and relaxation can be altered independently by acutely changing ventricular work loads (11). SUM …”
Section: Negative Pdmentioning
confidence: 99%
See 1 more Smart Citation